LEFT VENTRICULAR DEFORMATION IN PATIENTS WITH SYSTEMIC ARTERIAL HYPERTENSION BY 2D SPACKLE TRACKING ECHOCARDIOGRAPHY. (June 2018) - Gronkova-Zlatareva, N.; Dimitrova, V.; Petrov, I.; Tsonev, S.
Abstract : Objective: Systemic arterial hypertension represents an increase in cardiac afterload and the compensatory mechanism is the development of left ventricular concentric hypertrophy with diastolic dysfunction, and secondarily atrial dysfunction. The aim of our study is to evaluate the left ventricular mechanical deformation by 2D spackle tracking echocardiography and estimate left ventricular longitudinal and circumferential strain in the patients with systemic arterial hypertension. Design and method: We investigated 38 patients with systemic hypertension without heart failure, valvular or myocardial lesion and 36 healthy controls. The control group had no clinical symptoms, and the electrocardiogram and echocardiogram were normal. All patients had conventional transthoracic echocardiography following current guidelines and longitudinal and global longitudinal and circumferential strain by 2D speckle tracking. All statistical analyses were performed with SPSS version 17.0 Results: Statistically significant differences were not found between hypertensive and control patients in left atrial volume, inter-ventricular septum, posterior wall thickness, left ventricular diastolic diameter, left ventricular relative wall thickness, left ventricle mass index, E/A ratio, E/e[Combining Acute Accent] ratio, systolic pulmonary artery pressure. The global circumferential strain showed significantly decreased (p < 0.001) in the patients with arterial hypertension compared to the controlled group (−17.8 ± 4 versus - 20.4 ± 6). The longitudinal strain also significant decreases (p < 0.008) in the hypertensive patients (−20.38 ± 2.3 versus −22.30). Conclusions: In hypertensive patients the global longitudinal and global circumferential deformation was significantly decreased. The speckle tracking gives the knowledge of subclinical left ventricular dysfunction in hypertensive patients.